Document Addressed to Cardiovascular Echography Operators at the Time of COVID-19: A Document by the “Società Italiana di Ecocardiografia e CardioVascular Imaging” Board 2019–2021 - Antonini-Canterin, Francesco (J Cardiovasc Echogr, 2020)
The epidemic of COVID-19 has grown to pandemic proportions and the preventive and mitigation measures have been widely spread through the media. The cardiologists are called as consultants for the cardiovascular pathologies and echocardiography is a fundamental examination in many clinical situations, but not without risks for health staff. Società Italiana di Ecocardiografia e CardioVascular Imaging Council has decided to formulate a document aimed to highlight the importance of a correct indication and execution procedure of the echocardiogram during a COVID-19 pandemic.